Analisis Kebutuhan dan Potensi Masyarakat Desa Wisata Lantebung Sebagai Pemandu Wisata Lokal - Trully Dewanti Rumope; Yenny Susanto; Mia Rahayu (ITINERARY: Journal of Travel Operation and Travel Business, 2025)
This research aims: (1) to find out the main factors needed by the Lantebung Tourism Village community as a local tour guide. (2) to find out the obstacles faced by the Lantebung Tourism Village community as a local tour guide. This research uses descriptive qualitative methods. The variable in this study is the needs of the community as a tunuggal variable that is analyzed through indicators that include guiding training, mastery of attraction information, foreign language skills, support and ongoing assistance. Data were collected through interviews, observations, and documentation obtained directly from the research location. Data analysis techniques were obtained through the process of data reduction, data presentation, and conclusion drawing. The results of this study show: (1) some village communities, especially youths, have an interest in becoming local tour guides, (2) but they still face several obstacles, namely the lack of training in material interpretation, English language training, and the lack of assistance or supporting facilities from related parties